Pengaruh High Performance Work System terhadap Employee Performance dengan Organization Citizenship Behavior Sebagai Variabel Mediasi - Khafid, Abdul; Putra, Gilang Kharisma; Hastuti, Erma Sri (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2024)
Abstract The purpose of this study is to reveal the effect of high performance work systems on employee performance with Organization citizenship behavior as a mediating variable. using quantitative research methods. The research data was obtained from electronic questionnaires which were distributed online. For the sampling method using purposive sampling where this method is a sampling technique based on certain criteria, it was found that the respondents in this study totaled 92 respondents. The results of the R test show that the Organization citizenship behavior variable has an R Square value of 0.947 while for the employee performance variable it is 0.949. Testing the hypothesis proves that the high performance work systems variable has a positive and significant effect on employee performance, Organization citizenship behavior variable has a positive and significant effect on employee performance, High performance work systems variable has a positive and significant effect on Organization citizenship behavior variable and Organization citizenship behavior variable is proven to be able to mediate the relationship between High performance work systems and employee performance is positive and significant. These results are expected to be a reference for companies that are in the stage of building employee performance for maximum work results.Keywords: High Performance Work System, High Performance, Organization Citizenship Behavior.